Jointly navigating through RRI in practice: lessons from technology design - Menisha Patel; Sachini Weerawardhana; Luc Moreau (Journal of Responsible Innovation)
The potential of autonomous robots to assist humans in emergency situations remains a prominent area of innovation. However, such developments may present profound societal and ethical challenges. Ideally, an active integration of Responsible Research and Innovation (RRI) allows for harnessing innovation while mitigating the potential negative implications. We present an attempt by an interdisciplinary team with limited exposure to RRI to incorporate the approach into an academic project exploring autonomous robots. Our case study reveals the complexities emerging locally when translating and applying RRI to the procedural aspects and intended project outcomes. We discuss key issues that emerge and how the team navigates through these. We draw on insights from practice-oriented approaches, as in science and technology studies and sociology. We raise social and ethical questions and develop practice-oriented recommendations to facilitate the future integration of RRI into projects.